FAKTOR DETERMINAN STATUS KESEHATAN BAYI NEONATAL DI RSKDIA SITI FATIMAH MAKASSAR - Ahmad, Ekayanti Hafidah; Buraerah, .; Hakim, Abd.; Prawirodihardjo, Leo (Universitas Ahmad Dahlan, 2012)
Background : Aim of the research was to acknowledge the effect of neonatal baby weight, age of birth giving, breast milk feeding on neonatal babys health status.Methode : The research design was a cross sectional study, with interview method and homevisit of 160 respondents. Samples were withdrawn with simple random sampling method. Data was analyzed with simple linier regression test, continued with multiple linier regression test.Results : Results of the research indicated that the weight of neonatal baby, the age of birth giving mother, age of pregnancy, and breast milk feeding have influences on the neonatal babys health status. Of the four variables, two of them were observed to have dominant influences of the baby health status in neoantal period in Siti Fatimah RSKDIA Makassar, i.e (?) 0.374 p=0,000 (37.4%) and mother breast feeding (?) 0.306 p=0.000 (30.6%).Â Keywords : neonatal baby, mothers age, age of pregnancy, breast feeding